2014
DOI: 10.3998/ark.5550190.p008.632
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ligation from O-acyl isopeptides via 8- and 11-membered cyclic transition states

Abstract: Unprotected O-acylated serine and O-acylated threonine isopeptides have been synthesized, and their conversion to native tripeptides and tetrapeptides by O-to N-terminus transfer investigated. Ligations involving 8-and 11-membered cyclic transition states are shown experimentally and computationally to be more favorable than intermolecular cross-ligations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A feature of the homologated (β 3 ) amino acids used in 9 is that the size of the NCL [S–N] trans -acyl shift transition states differs from those used in the previously reported α-peptide-forming rotaxane machines . Katritzky found that NCLs requiring 15- or 19-membered [S–N] acyl-transfer transition states, the size employed in the operation of 9 , are significantly slower than NCLs involving 11-, 14-, and 17-membered transition states (which featured in the operation of the α-peptide-forming machines) . We attribute the longer reaction time necessary for complete operation of 9 (7 days, cf., 3 days for α-peptide-forming machines) to these less favorable transition-state sizes.…”
Section: Resultsmentioning
confidence: 99%
“…A feature of the homologated (β 3 ) amino acids used in 9 is that the size of the NCL [S–N] trans -acyl shift transition states differs from those used in the previously reported α-peptide-forming rotaxane machines . Katritzky found that NCLs requiring 15- or 19-membered [S–N] acyl-transfer transition states, the size employed in the operation of 9 , are significantly slower than NCLs involving 11-, 14-, and 17-membered transition states (which featured in the operation of the α-peptide-forming machines) . We attribute the longer reaction time necessary for complete operation of 9 (7 days, cf., 3 days for α-peptide-forming machines) to these less favorable transition-state sizes.…”
Section: Resultsmentioning
confidence: 99%
“…Homocysteine-containing isopeptide 19 was also prepared, and ligation via a 6-membered cyclic transition state was studied. The formation of ligated product with 98% abundance was observed by HPLC-MS analysis, showing that S → N -acyl group migration via a 6-membered transition state is preferred over intermolecular acylation (Scheme ) …”
Section: Chemical Ligations From Cysteine Isopeptidesmentioning
confidence: 99%